ANALYSIS OF ECONOMIC ACTIVITY MOVEMENTS IN THE CZECH REPUBLIC – FREQUENCY APPROACH - Poměnková, Jitka (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
The primary purpose of this work is to identify the business cycletypes in the Czech Republic. In the light of business cycles problematic, andviewed from the frequency analysis perspective, harmonic analysis will beused. From the range of de-trending techniques, the first order difference,linear filtering, unobserved component model and Hodrick-Prescott filter areused. In the case of Hodrick-Prescott filter, a cyclical fluctuation estimatewith the derivation of smoothing parameter designed specially for the CzechRepublic case is investigated. The aim is to distinguish types of cyclicalfluctuations in the Czech Republic. A consequent analysis of potentialsources of cyclical movement is done